Influence of depression, anxiety and stress on the quality of life of dialysis patients - Musa, Ramli; Liu , Wen Jinn; Bujang, Adam; Mohd Zaher, Zaki Morad; Thian Fook, Chew (2014)
Background: Depressive Anxiety and Stress Scale (DASS-21) is considered as a suitable tool to be used in the clinical practice and/or research. The use of DASS-21 as a higher-order measure of psychological distress was supported by the data in the first part of this study. In the present study the three constructs of DASS have been used in predicting the quality of life of patients undergoing dialysis. Method: A Cross-sectional survey. The DASS-21 scale was administered to 1,333 patients undergoing renal dialysis. In assessing the influence of DAS on the Quality of life of the Malaysian population who are experiencing series of renal dialysis, competing models of latent structures of Depression, Anxiety and Stress Scale-21 item (DASS-21) and World Health Organization Quality of Life BREF scale (WHOQOL-BREF were evaluated using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). Objectives: Main objective was to validate the WHOQOL-BREF scale and DASS-21 as the first stage of SEM in developing and testing the structural model of Predictors of the Quality of Life (POQOL) of Malaysian patients undergoing series of Renal Dialysis. Secondly to meet high psychometric standards of both measurement models and the SEM model of POQOL. Results: Through CFA and SEM, the current study produced shorter scales i.e. from 26 items of WHOQOL-BREF to QOLS-13; and from DASS-21 to DASS-13. Results proved that the three constructs of the modified QOLS-13 and three constructs of the modified DASS-11 met high psychometric standards hence, gave a go-ahead to use them in developing the model of POQOL which also proved to have met high psychometric standards. Results showed a very significant inter-relationship between depression, anxiety and stress; and a significant influence of DASS-11 on the three significant inter-related constructs of the QOL-13. Conclusion: The model of Predictors of the Quality of life (POQOL) has been able to meet high psychometric standards and therefore recommended to be used in assessing the influence of Psychological Distress on the Quality of Life.